2020
DOI: 10.2147/ndt.s276203
|View full text |Cite
|
Sign up to set email alerts
|

<p>Virtual Reality Exposure Therapy (VRET) for Anxiety Due to Fear of COVID-19 Infection: A Case Series</p>

Abstract: Virtual reality exposure therapy (VRET) is becoming popular for treating phobia and anxiety disorder. The recent pandemic of COVID-19 not only causes infection per se but also has an impact on mental health. This case series aimed to explore the role of VRET in the intervention of psychiatric illnesses with chief complaints of fear of COVID-19 infection. In vivo exposure therapy for fear of COVID-19 infection is not possible due to the risk of virus infection; in this scenario, the VRET provides an immersive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…One case-series study (Zhang et al, 2020 ) investigated the effects of VR exposure therapy reducing anxiety due to COVID-19 infection in three participants. Anxiety symptoms decreased significantly at post-treatment; phobic symptoms (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…One case-series study (Zhang et al, 2020 ) investigated the effects of VR exposure therapy reducing anxiety due to COVID-19 infection in three participants. Anxiety symptoms decreased significantly at post-treatment; phobic symptoms (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the impacts, if not all, can be addressed by expanding the integration of DHTs into clinical workflows, and efforts to develop DHTs specifically targeting mental healthcare during COVID-19 have been seen in China. For example, online interventions for situational insomnia ( Zhang et al, 2021a ) and common mental health problems ( Song et al, 2021 ) during the pandemic, a virtual reality exposure therapy for fear of COVID-19 infection ( Zhang et al, 2020b ), and a peer support programme for frontline healthcare workers via social media ( Cheng et al, 2020 ), were developed and tested. Almost all respondents agreed that DHTs were useful during the pandemic and expressed high levels of willingness to use DHT after the pandemic, suggesting that adopting DHTs for clinical services may be a promising solution for China's mental health services to deal with the new normal.…”
Section: Discussionmentioning
confidence: 99%
“…65 The 4 case studies assessed the efficacy of emotional support plus progressive muscle relaxation therapy, 27 interpersonal psychotherapy, 36 dialectical behaviour therapy, 82 and virtual reality exposure therapy. 49 Target outcomes. Our review finds that anxiety, depression, and stress-related disorders are commonly observed following disasters and are frequently the focus of post-disaster MHPSS interventions.…”
Section: Methods Used To Assess the Outcome Of Mhpss Intervention Stu...mentioning
confidence: 99%
“…35,37,38,47 Other frequently mentioned psychotherapies include interpersonal therapy, 30,36 cognitive therapy, 26,27 and exposure therapy. 49,77 Psychopharmacological interventions (including treatment with alprazolam, paroxetine, diazepam and Chinese herbal formulae) were used in four studies. 26,51,78,79 Mental health education, psychological counselling, and other supportive interventions.…”
Section: Types Of Interventions Used In Mhpss Intervention Studiesmentioning
confidence: 99%